Development of Songs in the Wayang Kulit Performances of Sanggar Hamiluhung In Kubu Raya Regency - Revinta; Ghozali , Imam; Dihita Sagala, Mastri (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2026)
Wayang Kulit is a cultural heritage that has been recognized internationally. This study reveals the development of songs in certain sections of the Wayang Kulit performances of Sanggar Hamiluhung. The method used in this research is qualitative descriptive with an ethnomusicological approach. Data were collected through interviews, observation, and documentation study. The validity of the data was tested using source triangulation and prolonged observation, while data analysis employed the steps proposed by Miles and Huberman. The results show that the songs in the goro-goro section of the Wayang Kulit performance are developed beyond the standard repertoire. The developed songs are created through a musical arrangement process. The instruments used have also been expanded from the traditional set by adding modern instruments. The duration of the goro-goro section has likewise been extended. The development of the songs is influenced by artists' creativity, community interest, and technological support. The findings of this study indicate that the development of songs does not occur suddenly but rather through a long process. This research can be used as one of the efforts to preserve the Wayang Kulit art form. In order for this art form to be widely accepted by society, continuous education, the regeneration of artists through learning in formal and non-formal education, as well as community- or studio-based training, are required.